Father : a dramatic teleplay. - Santa Maria, Samantha. (2009)
Father...a thirty-three year old, newly-ordained priest, Father Thomas Samuel, is assigned to his first parish. From the outset, he is a true believer, with an almost childlike faith in a fair and just God. His faith is tested when he has to lie to a dying woman to give her her final comfort and peace, supervise a church choir which turns out to be a nest of petty Church politics and baptize a deformed child whom he secretly wishes death on. The climax takes place when he has to preside over midnight Mass on Christmas and sees the people who have been a part of these three tests. They remind him that his perception of God has been incorrect, that he has been deceived and that the teachings he believes in, Or once believed in, has fallen on deaf ears. His faith crumbles at that moment, and he recites the introductory rite without feeling. He loses his childlike faith and becomes indifferent.